Effect of Cathodal Transcranial Direct Current Stimulation on a Child with Involuntary Movement after Hypoxic Encephalopathy - Mayumi Nagai; Naofumi Tanaka; Yutaka Oouchida; Shin-Ichi Izumi (Case Reports in Medicine)
The aim of the study was to investigate the effect of cathodal transcranial direct current stimulation to the supplementary motor area to inhibit involuntary movements of a child. An 8-year-old boy who developed hypoxic encephalopathy after asphyxia at the age of 2 had difficulty in remaining standing without support because of involuntary movements. He was instructed to remain standing with his plastic ankle-foot orthosis for 10 s at three time points by leaning forward with his forearms on a desk. He received cathodal or sham transcranial direct current stimulation to the supplementary motor area at 1 mA for 10 min. Involuntary movements during standing were measured using an accelerometer attached to his forehead. The low-frequency power of involuntary movements during cathodal transcranial direct current stimulation significantly decreased compared with that during sham stimulation. No adverse effects were observed. Involuntary movement reduction by cathodal stimulation to supplementary motor areas suggests that stimulations modulated the corticobasal ganglia motor circuit. Cathodal stimulation to supplementary motor areas may be effective for reducing involuntary movements and may be safely applied to children with movement disorders.